Securitization of the sectarianism in Iraq: A Study of the Overlap of Intellectual and Regional Dimensions from the Perspective of the Copenhagen School - طه عثمان, تارا (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Security studies in international relations developed in the period following the two world wars, and external threats to the state formed the focus of the topics and principles on which security studies were based in the first era. In the period in which the world witnessed the end of the Vietnam War, the opening of research centers specialized in security affairs, in addition to the launch of new visions and theories, security studies shifted towards a new era based on the principles of deepening and expanding security. If insecurity requires studying existing threats and trying to reduce them, the real study of security in the following period meant reformulating what is considered a threat. In this context, the threats may not actually exist, and what presents and formulates them as security threats is our vision of it in a certain way. This development in the concept created another concept, namely the concept of (securitization), which is one of the concepts put forward within the views of (Copenhagen School).